Problemy fonostylistyki w twórczości poetyckiej Wielimira Chlebnikowa - Górska, Monika (Studia Rossica Posnaniensia, 2011)
The article presents an attempt to analyse Velimir Khlebnikov's selected poems from the point of view of phonostylistic, i.e. sound and prosodic organization. In the poet's texts, sound can be said to have three main functions: onomatopoeic, conceptual, and structural. Each is present in Khlebnikov's texts, but none of them manifests to the same degree. A detailed analysis of these texts with respect to phonostylistic elements reveals a number of meanings absent from many other analyses, and many times proves to be the exclusive method of comprehension of Khlebnikov's texts.